(untitled) (Konferensiyalar | Conferences, 2024)
This study explores the effectiveness of utilizing e-platforms for teaching English language to mixed-level students. It investigates various e-platforms such as online courses, virtual classrooms, and interactive learning tools. The research aims to assess the impact of these platforms on students’ language acquisition, engagement, and overall learning outcomes. Additionally, it examines strategies and techniques used by educators to cater to the diverse needs and proficiency levels of students in the online environment. Through qualitative and quantitative analysis, the study seeks to provide insights into the challenges and opportunities associated with teaching English through e-platforms to a heterogeneous group of learners.